2012
DOI: 10.1097/mpa.0b013e318221c91b
|View full text |Cite
|
Sign up to set email alerts
|

Pancreaticoduodenectomy Versus Duodenum-Preserving Pancreatic Head Resection for the Treatment of Chronic Pancreatitis

Abstract: Both procedures are equally effective in pain relief, but DPPHR is superior to PD in operative data, postoperative morbidity, improving quality of life, and preservation of exocrine and endocrine function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 39 publications
1
17
0
4
Order By: Relevance
“…Many previous studies revealed that the duodenum‐preserving procedure had significant benefits with regard to a low level of postoperative morbidity and mortality, the maintenance of pancreatic endocrine and exocrine functions, a low frequency of DGE and a higher quality of life score . However, our results yielded conflicting conclusions regarding the postoperative morbidity of DPPHR.…”
Section: Discussionmentioning
confidence: 55%
“…Many previous studies revealed that the duodenum‐preserving procedure had significant benefits with regard to a low level of postoperative morbidity and mortality, the maintenance of pancreatic endocrine and exocrine functions, a low frequency of DGE and a higher quality of life score . However, our results yielded conflicting conclusions regarding the postoperative morbidity of DPPHR.…”
Section: Discussionmentioning
confidence: 55%
“…Two studies 22,27 have initially estimated the sample size for study. For the 10 observational studies, [17][18][19]21,24,25,[28][29][30][31] the risks of bias were evaluated by modification of the Newcastle-Ottawa Scale.…”
Section: Quality Of Included Studiesmentioning
confidence: 99%
“…The Partington and Rochelle procedure is common in surgical practice, with low morbidity and mortality. However, approximately 20% of patients with CP have a dominant inflammatory mass within the pancreatic head, which is identified as the leading site of the disease and causes the pain sensations of some patients [9]. The Frey procedure has been recommended by many surgical scholars because it allows for better pain relief than the Partington and Rochelle procedure [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…However, approximately 20% of patients with CP have a dominant inflammatory mass within the pancreatic head, which is identified as the leading site of the disease and causes the pain sensations of some patients [9]. The Frey procedure has been recommended by many surgical scholars because it allows for better pain relief than the Partington and Rochelle procedure [9,10]. Therefore, we also chose the Frey procedure, even without inflammatory masses at the pancreatic head, and there were no differences between the 2 procedures in terms of the time of operation, volume of lost tissue, or rate of early complications.…”
Section: Discussionmentioning
confidence: 99%